Research on near-field focusing algorithm of reconfigurable reflect-array - Liu, HongYan; Zheng, Pei; Wang, Chao; Guo, Lei; Zhang, XinYu (Journal of engineering (Stevenage, England), 2019)
In this study, the near-field beam focusing algorithm of reconfigurable reflect array for security imaging application is proposed. The proposed near-field focusing algorithm is based on classic array method, which is usually adopted for far-field pattern calculation. In order to satisfy the near-field imaging application, the imaging distance is added to array method, and the improved formula can calculate the shifting phase of every array element precisely. In addition, due to discrete phase characteristic of reconfigurable reflect array, a phase choice method based on trigonometric function is used in authors’ design. Based on the proposed algorithm, the shifting phase of every element is calculated and obtained the simulated beam focusing patterns. Meanwhile, the calculated shifting phase is written to whole array by field-programmable gate array, the near-field beam scanning patterns is measured and the measured results are in good agreement with the simulated ones.